Tea Production Response to Climate Change in Kenya: An Autoregressive Distributed Lag Approach - Kariuk, George Mbugua; Njaramba, Jennifer; Ombuki, Charles (AJER, 2022)
Tea sector plays a critical role in socio economic development in Kenya. It is a leading foreign exchange earner, a major source of livelihood for most rural communities and significantly contributes to poverty reduction. However, in the last three decades there has been , unstable trends in tea production that has been linked to climate driven stresses. Over the last two decades, tea producing areas in Kenya have been exposed to extreme climate events that include temperature rise, eractic rainfall and growing incidence of extreme weather events such as hail storms, drought and frost. These events are expected to have adverse effects on the largely rainfed tea production with potentially irreversible socio economic effects. This study sought to ascertain the effects of climate change on tea production in Kenya while controlling for economic incentives. The study adopted the Autoregressive distributed lag econometric modeling approach using data for the period between 1979 and 2019. The findings indicate that rainfall being experienced in the usual dry period of January and February, price of tea, and area under tea crop, have a positive and significant effect on tea production. However, rainfall variability, rainfall amount in extended long rain periods, maximum temperature, spending on agricultural development, real effective exchange rate, and price of fertilizer have a negative effect on tea production. Given the negative effects of climate change on tea production, there is a need for collaborative efforts towards developing definite, viable and sustainable adaptation options targeting tea farming
Keywords: Tea production; Climate Change; ARDL; Rainfall Variability; Temperature Variability